Components of the pelleting system - Fairchild, Fred J. (My University, 2015)
This article will address the components in a pelleting system for animal feed. It will be a walk-through of a system. Specific information and features about different pieces of equipment used in the system will be addressed in a future article. A diagram of a typical pelleting system is shown in Figure l.
Keywords: Feed processing; Feed pellets; Pellet mill